2012
DOI: 10.1017/s1368980012003047
|View full text |Cite
|
Sign up to set email alerts
|

Flour fortification with iron has no impact on anaemia in urban Brazilian children

Abstract: Objective: To verify the impact of flour fortification on anaemia in Brazilian children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
2
14

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 16 publications
3
32
2
14
Order By: Relevance
“…The extent of its use is due to the low cost and stability when added in flour. The low bioavailability of this source may explain the findings of Assunção and colleagues (27) who showed that Fe fortification in Brazil had no impact on anaemia in children under 6 years old living in the urban area of the city of Pelotas, southern Brazil. Hurrell et al (8) reviewed the efficacy and effectiveness studies with various Fe-fortified foods and found strong evidence that reduced Fe and other forms of Fe with low bioavailability cannot be efficacious to a have satisfactory impact on Fe status.…”
Section: Discussionmentioning
confidence: 98%
“…The extent of its use is due to the low cost and stability when added in flour. The low bioavailability of this source may explain the findings of Assunção and colleagues (27) who showed that Fe fortification in Brazil had no impact on anaemia in children under 6 years old living in the urban area of the city of Pelotas, southern Brazil. Hurrell et al (8) reviewed the efficacy and effectiveness studies with various Fe-fortified foods and found strong evidence that reduced Fe and other forms of Fe with low bioavailability cannot be efficacious to a have satisfactory impact on Fe status.…”
Section: Discussionmentioning
confidence: 98%
“…Sugere-se que o impacto desse programa tenha sido mais favorável às crianças maiores em virtude de uma quantidade mais elevada do consumo desses alimentos enriquecidos 8,9 . Contrapondo-se a essa hipótese, os estudos de Pelotas, Rio Grande do Sul 20,21 , não observaram diferença significativa entre os momentos antes e após a fortificação obrigatória das farinhas em crianças de 12 a 24 meses. No entanto, como o Brasil é um país de vasta extensão geográfica e diversidades culturais, econômicas e sociais, a necessidade de outros estudos é inegável para avaliar de fato o efeito da suplementação das farinhas em nível nacional.…”
Section: Introductionunclassified
“…In a study conducted in Pelotas with children under 6 years old, there was no evidence of the effect of flour fortification on Hb levels, which remained constant, and the prevalence of anemia, contrary to what was expected, increased from 30.2 to 42.6% after 3 years of implementation of fortification [28]. However, Costa et al [29] observed that 2 years after the implementation of fortification, the prevalence of anemia in preschool children attending the Early Childhood Education Centers in the municipality of Sao Paulo was 20.9%; a value significantly lower compared to the anemia rate of 63% in a previous study conducted in the same region.…”
Section: Discussionmentioning
confidence: 80%